2002
DOI: 10.1046/j.1439-0388.2002.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

Genotype by environment interaction for milk yield in Sarda dairy sheep

Abstract: Genotype by environment interaction (GEI) for milk yield (ME) was investigated by analyzing 40 140 first lactation records performed in 538 flocks. Flock-year effects from national genetic evaluation were used to define low (L), medium (M) and high (H) yielding environments. Differences observed between adjacent subsets were approximately 20% of the trait overall mean. Sire variance components estimated using multitrait analysis were 58, 82 and 149% of the estimate from the complete dataset (L, M and H, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
(21 reference statements)
1
7
0
1
Order By: Relevance
“…However, R 2 s reported in the literature were mostly higher. In Sarda, Florina and Assaf sheep, Sanna et al (1994), Christodoulou et al (1997), and Gootwine and Pollot (2002) reported R 2 s from 0.55 through 0.57 to 0.75. In White Shorthaired goats, Margetín and Milerski (2000) reported R 2 s from 0.65 to 0.79 (depending on either herd and year or herd-year-season effects involved).…”
Section: Resultsmentioning
confidence: 96%
“…However, R 2 s reported in the literature were mostly higher. In Sarda, Florina and Assaf sheep, Sanna et al (1994), Christodoulou et al (1997), and Gootwine and Pollot (2002) reported R 2 s from 0.55 through 0.57 to 0.75. In White Shorthaired goats, Margetín and Milerski (2000) reported R 2 s from 0.65 to 0.79 (depending on either herd and year or herd-year-season effects involved).…”
Section: Resultsmentioning
confidence: 96%
“…In general, the model choice had implications in the selection of the best animals, particularly when considering different environments. Sanna et al (2002), in a study with Sarda dairy sheep, pointed out changes in genotype ranking, as well as changes in the absolute and relative magnitude of variance between environments, suggesting the existence of G9E for milk yield in rearing conditions.…”
Section: Discussionmentioning
confidence: 98%
“…When such strong maternal effects differ between the sexes, they can bias evolution of sexual size dimorphism in several ways (Rutledge et al 1972;Lande and Kirkpatrick 1990;Meyer 1992;Quintanilla et al 1999;Sanna et al 2002). First, the interaction (negative or positive) between maternal effects and additive genetic variance in either sex can bias a trait response to selection.…”
Section: Inheritance Of Parental Adaptations and The Environment Of Ementioning
confidence: 99%